Neoliberal Welfare Reform, Poverty and Adult Education: Identifying the Problem and Engaging in Resistance - Mary Alfred; Shauna Butterwick; Catherine Hansman; Jenny Sandlin (Adult Education Research Conference, 2007)
This symposium explores the foundation of neoliberal ideology which has been central to the reform of welfare and adult education policies programs and the increase in poverty and oppression. We outline of an alternative vision, informed by a feminist social justice orientation